2016
DOI: 10.1186/s12985-016-0647-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection and differentiation of three genotypes of Brassica yellows virus by multiplex reverse transcription-polymerase chain reaction

Abstract: BackgroundBrassica yellows virus (BrYV), proposed to be a new polerovirus species, three distinct genotypes (BrYV-A, BrYV-B and BrYV-C) have been described. This study was to develop a simple, rapid, sensitive, cost-effective method for simultaneous detection and differentiation of three genotypes of BrYV.ResultsIn this study, a multiplex reverse transcription-polymerase chain reaction (mRT-PCR) was developed for simultaneous detection and differentiation of the three genotypes of BrYV. The three genotypes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Brassica yellows virus (BrYV) is a tentative newly identified species in the genus of Polerovirus , and it is closely related to turnip yellows virus (TuYV) [ 8 , 9 ]. It is spread widely throughout China as well as in South Korea and Japan [ 4 , 10 , 11 ]. BrYV has a wide host range, although it mainly infects Brassicaceae crops, including cabbage ( Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brassica yellows virus (BrYV) is a tentative newly identified species in the genus of Polerovirus , and it is closely related to turnip yellows virus (TuYV) [ 8 , 9 ]. It is spread widely throughout China as well as in South Korea and Japan [ 4 , 10 , 11 ]. BrYV has a wide host range, although it mainly infects Brassicaceae crops, including cabbage ( Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…botrytis ), mustard ( B. juncea ), and turnip ( Raphanus sativus var. oleifera ), usually causing leaf malformations and yellowing in the field [ 4 , 9 , 10 , 11 , 12 ]. BrYV has at least three genotypes (BrYV-A, B, and C) as determined by sequence analyses, and full-length infectious cDNA clones of these three genotypes have been developed successfully [ 8 , 10 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of host range, CaMV ranks second only to TuMV, based on the number of susceptible hosts among vegetable brassicas (Spence et al 2007). CMV has extremely wide host range, and is one of the main pathogens of cruciferous crops (Zhang et al 2016). CMV is efficiently transmitted by more than 75 species of aphids in non-persistent manner (Krenz et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…genotypes (BrYV-A, B, and C) according to sequence analysis, the full-length infectious cDNA clones of these three genotypes have been developed successfully [8,[10][11][12][13]. Previously work have shown that the full-length amplicon of the virus has been successfully transferred into Arabidopsis thaliana and obtained stable genetically transgenic lines named 111 and 412 which all exhibited severe symptoms including dwarfing and the purple leaves [14].…”
mentioning
confidence: 99%